Laporan hasil survei pengembangan budidaya ikan air tawar di Sumatera Barat (Team Survei Direktorat Jenderal Perikanan ; Dinas Perikanan Daerah Tk. I Sumatera Barat, 1983)
Report on the results of a survey for the development of fresh water pisciculture in West Sumatra.